Protein pattern of canola (Brassica napus L.) changes in response to salt and salicylic acid in vitro - Razavizadeh, Roya (Biological Letters, 2016)
The effect of salicylic acid (SA) on the salt (NaCl) tolerance mechanism was studied in canola plants (oilseed rape, Brassica napus L.) by molecular and physiological experiments in plant tissue culture. Seeds of B. napus ‘Ocapy’ were germinated at 0, 50, and 100 mM NaCl on Murashige and Skoog (MS) medium containing different levels (0, 2, and 5 μM) of SA for 4 weeks. Total chlorophyll, carotenoid, and flavonoid content increased in response to interactive effects of SA and NaCl treatments at some concentrations. Proline content was increased under salt and SA treatments in shoot and root tissues. Salt alone and in combination with SA increased the total soluble protein content of shoots only, while the different concentrations of SA in the culture media affected variously the total soluble protein content. Protein patterns of shoots and roots showed some remarkable differences, based on gel electrophoresis and the consequent analysis of bands by ImageJ program. The relative expression of 15 and 12 protein bands in shoots and roots, respectively, differed under the applied treatments. In addition, the protein profile indicated that salinity and SA regulate the expression of salt-stress-inducible proteins as well as induced de novo synthesis of specific polypeptides. The findings may help to explain the salt tolerance mechanisms and to produce salt-tolerant canola plants.